Evaluation of The Current Level of Knowledge of The Residents of Dhaka City Regarding Earthquake Hazard - Santo, Saif Ahmed; Fariha, Akhi Sultana; Hossain, Md. Rakib; Shah, Syed Emon (Universitas Sanata Dharma, 2023)
An earthquake is a sudden disaster that is not possible to predict. This impulsive behavior makes it very dangerous for humankind. Precautionary measures are immense for reducing damage. The first step of preventive measures for an earthquake is raising awareness. Dhaka City has a high earthquake risk due to its large population and urbanization. Researchers have said that an earthquake in this zone can be fatal, resulting in heavy casualties with structural damage. For this reason, proper awareness is essential for the residents of this area. This study shows an insight into the knowledge level of the residents of Dhaka City regarding earthquake incidents. Survey data indicates that many people lack Knowledge of what to do before and during an earthquake. Especially school and college-going students are unaware of the essential things to do during an earthquake incident. Many people still don’t know the importance of a seismic-resistant building system and are unprepared for a seismic event. This study brings these aspects together to learn about the knowledge level, which can help policymakers raise awareness among this city's residents.